Liminalidad e interculturalidad en la poesía de Pedro S. Zulen: entre la contemplación oriental y la modernidad occidental - Peláez Sagástegui, Elizabeth (2025)
The essay proposes a hermeneutic and comparative reading of three texts from El olmo incierto de la nevada (1930) by Pedro S. Zulen: the prose poem of the same title, “El poema de una lágrima” and “Humano fragor”. The analysis is framed within “liminal experience” (Turner), understood as a threshold between Western and Eastern cultural, literary, and aesthetic traditions. Drawing on studies of literary Orientalism, modernist cosmopolitanism, and the reception of haiku in Peru, it explores how Zulen’s poetics intertwine Eastern and Western sensibilities, generating a hybrid subjectivity.